Contribution of audiovestibular tests to the topographic diagnosis of sudden deafness - Oiticica, Jeanne; Bittar, Roseli Saraiva Moreira; Castro, Claudio Campi de; Grasel, Signe; Pereira, Larissa Vilela; Bastos, Sandra Lira; Ramos, Alice Carolina Mataruco; Beck, Roberto (International Archives of Otorhinolaryngology, 2013)
Introduction: Sudden hearing loss (SHL) is an ENT emergency defined as sensorineural hearing loss (SNHL) ≥ 30 dB HL affecting at least 3 consecutive tonal frequencies, showing a sudden onset, and occurring within 3 days. In cases of SHL, a detailed investigation should be performed in order to determine the etiology and provide the best treatment. Otoacoustic emission (OAE) analysis, electronystagmography (ENG), bithermal caloric test (BCT), and vestibular evoked myogenic potential (VEMP) assessments may be used in addition to a number of auxiliary methods to determine the topographic diagnosis.Objective To evaluate the contribution of OAE analysis, BCT, VEMP assessment, and magnetic resonance imaging (MRI) to the topographic diagnosis of SHL.Method Cross-sectional and retrospective studies of 21 patients with SHL, as defined above, were performed. The patients underwent the following exams: audiometry, tympanometry, OAE analysis, BCT, VEMP assessment, and MRI. Sex, affected side, degree of hearing loss, and cochleovestibular test results were described and correlated with MRI findings. Student's t-test was used for analysis of qualitative variables (p < 0.05).Results The mean age of the 21 patients assessed was 52.5 ± 15.3 years; 13 (61.9%) were women and 8 (38.1%) were men. Most (55%) had severe hearing loss. MRI changes were found in 20% of the cases. When the audiovestibular test results were added to the MRI findings, the topographic SHL diagnosis rate increased from 20% to 45%.Conclusion Only combined analysis via several examinations provides a precise topographic diagnosis. Isolated data do not provide sufficient evidence to establish the extent of involvement and, hence, a possible etiology.
Keywords: Deafness; Hearing Loss; Sudden; Diagnosis; Vestibular Function Tests; Hearing Tests